Therapeutic time window of minimally invasive surgery for intracerebral hemorrhage - Guangyu Guo; Wenliang Guo; Yangyang Feng; Hong Deng; Ping Zhang; Yingxin Tang; Guofeng Wu; Qi Li; Chao Pan; Zhouping Tang (Brain Hemorrhages, 2020)
Since mass effect and secondary brain injuries persist in the pathogenesis of intracerebral hemorrhage, hematoma evacuation within a limited time is reasonable. However, it is complex to define an accurate therapeutic time window (TTW) for hematoma evacuation. In this review, studies about TTW were discussed from four aspects: histopathology, molecular pathophysiology, neuroimaging and clinical outcomes. Animal experiments indicated that 6–12 h is the pathophysiological TTW of minimally invasive surgery. Clinical trials suggested that there is a correlation between TTW and clinical outcomes, while the exact TTW is still unclear due to lack of sufficient clinical studies, which deserves further investigation.